HUBUNGAN ANTARA SELF ESTEEM DENGAN FOMO PADA REMAJA - Siti Qurotul A'yun; Navyta Ramadhani Bukhroni Putri; Jannatus Syarifah; Moh. Soleh Murahman; Ari Khusumadewi (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to examine the relationship between self-esteem and the fear of missing out (FOMO) among adolescents who actively use social media, focusing specifically on tenth-grade students at SMAN 3 Jombang. Growing concerns regarding FOMO among teenagers highlight the need to investigate psychological factors that may contribute to its emergence. Employing a quantitative correlational design, the study involved 108 participants selected through purposive sampling. Two standardized psychological scales were utilized to measure levels of self-esteem and FOMO. Data were collected through self-administered questionnaires and analyzed using the Kolmogorov–Smirnov normality test and Spearman correlation analysis. The findings reveal no significant relationship between the two variables, as reflected by a correlation coefficient of –0,107 and a significance value of 0,272. These results indicate that self-esteem does not serve as a primary predictor of FOMO among adolescents. The study concludes that other psychological or social factors may play a more prominent role in shaping FOMO within this population. Future research is encouraged to explore additional variables such as social comparison, emotional regulation, patterns of social media use, and potential mediating or moderating mechanisms to provide a more comprehensive understanding of FOMO among adolescents.